If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13(y + -3) = 3(4y + 9y) + -66 Reorder the terms: 13(-3 + y) = 3(4y + 9y) + -66 (-3 * 13 + y * 13) = 3(4y + 9y) + -66 (-39 + 13y) = 3(4y + 9y) + -66 Combine like terms: 4y + 9y = 13y -39 + 13y = 3(13y) + -66 Remove parenthesis around (13y) -39 + 13y = 3 * 13y + -66 Multiply 3 * 13 -39 + 13y = 39y + -66 Reorder the terms: -39 + 13y = -66 + 39y Solving -39 + 13y = -66 + 39y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-39y' to each side of the equation. -39 + 13y + -39y = -66 + 39y + -39y Combine like terms: 13y + -39y = -26y -39 + -26y = -66 + 39y + -39y Combine like terms: 39y + -39y = 0 -39 + -26y = -66 + 0 -39 + -26y = -66 Add '39' to each side of the equation. -39 + 39 + -26y = -66 + 39 Combine like terms: -39 + 39 = 0 0 + -26y = -66 + 39 -26y = -66 + 39 Combine like terms: -66 + 39 = -27 -26y = -27 Divide each side by '-26'. y = 1.038461538 Simplifying y = 1.038461538
| 8+b+7b=40 | | 42=2m+3m-8 | | -5+t-5t=-37 | | 2n-2+n=-23 | | 6-7x-5x=-126 | | 6+b+3b=54 | | 8+5a+3a=40 | | 12x+2=2(4x+1)-x+7 | | 2m-9+3m=51 | | -4n-10-2n=-76 | | 5n+6+n=0 | | 36=m+3m+4 | | -28=3w+4w-7 | | 4x-6+2x=42 | | 5+2x+x=29 | | 33-9n=5-2n | | 10-7n-6n=62 | | 5+d+6d=75 | | 4=4m-5m+9 | | -2n+8+3n=-4 | | 5m+8+3m=-8 | | 7-7b+6b=8 | | 7-7d+6d=17 | | 1/2x-8=5 | | -106=4t+7t+4 | | 8-4m+6m=8 | | 60=4a+2a+6 | | 45=2d+6d+5 | | 5+d+6d=26 | | -12=-3k+5k+4 | | 4+7a+3a=-66 | | 32=-5n+7n+10 |